Direct Social Actions in Extreme Right Mobilisations. Ideological, strategic and organisational incentives in the Italian neo-fascist right - Froio, Caterina; Castelli Gattinara, Pietro (PARTECIPAZIONE E CONFLITTO, 2017)
Social movements scholarship has increasingly turned to the study of direct social actions (DSAs) in times of economic hardship. This paper broadens this perspective to extreme right organisations. Combining a Political Claims Analysis of newspaper articles and online press releases, with a qualitative discussion of online propaganda material, we explore the engagement in direct social activism by three neo-fascist organisations in Italy: Forza Nuova, Fiamma Tricolore and CasaPound Italia (1996 -2015). Our findings suggest that their propen-sity to direct social activism, rather than being exclusively related to economic distress, responds to a broad set of ideological, organisational and strategic incentives. Ideologically, DSAs are linked to the interpretation of the relationship between ideas and action of historical Fascism and of parts of the Italian neo-fascist tradition. Organisationally, DSAs serve as a tool to build support and solidarity, especially at the local level. Strategically, they are used to frame activism as a direct intervention in defence of interests of native peoples, and against political elites accused of being unresponsive to the needs of citizens. Our results offer a first empirical observation of the use of DSAs by extreme right actors, paving the way for comparative work at the cross-national level and on different arenas of engagement